1984
DOI: 10.1063/1.864695
|View full text |Cite
|
Sign up to set email alerts
|

A class of rotating compact tori equilibria

Abstract: A class of semi-analytical equilibria for rotating compact tori with toroidal current density vanishing at the separatrix is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 6 publications
1
40
0
Order By: Relevance
“…Since for fusion plasmas the thermal conduction along B is expected to be fast in relation to the heat transport perpendicular to a magnetic surface, equilibria with isothermal magnetic surfaces are a reasonable approximation [17,18,19,20,21,22]. In particular, the even simpler case of isothermal resistive equilibria has also been considered [23].…”
Section: B Isothermal Magnetic Surfacesmentioning
confidence: 99%
“…Since for fusion plasmas the thermal conduction along B is expected to be fast in relation to the heat transport perpendicular to a magnetic surface, equilibria with isothermal magnetic surfaces are a reasonable approximation [17,18,19,20,21,22]. In particular, the even simpler case of isothermal resistive equilibria has also been considered [23].…”
Section: B Isothermal Magnetic Surfacesmentioning
confidence: 99%
“…The equations for axisymmetric plasmas with pure toroidal flow and anisotropic pressure are recovered when F vanishes (Mercier and Cotsaftis 1961, Clemente 1993, 1994. Isotropic pressure equilibria with pure toroidal rotation are described when F = σ − = 0 (Maschke and Perrin 1980, Clemente and Farengo 1984, Viana et al 1997.…”
Section: Discussionmentioning
confidence: 99%
“…Although equilibrium studies of flowing plasmas began in the mid 1950s (e.g. Grad 1960), since the early 1980s there has been an increasing interest in the investigation of the equilibrium properties of plasmas with mass flow (Zehrfeld and Green 1972;Maschke and Perrin 1980;Morozov and Solovév 1980;Hameiri 1983;Clemente and Farengo 1984;Semenzato et al 1984;Kerner and Tokuda 1987;Throumoulopoulos and Pantis 1989;Avinash et al 1992;Żelazny et al 1993;Throumoulopoulos and Pantis 1996;Throumoulopoulos and Tasso 1997) which was motivated by the observation of plasma rotation in many tokamaks heated by neutral beams (Suckewer et al 1979;Brau et al 1983;Core et al 1987;Scott et al 1989;Tammen et al 1994) With the adoption of a specific equation of state, e.g. isentropic magnetic surfaces (Morozov and Solovév 1980), the axisymmetric ideal MHD equilibrium states obey to a partial differential equation for ψ, containing five surface quantities, in conjunction with a nonlinear algebraic Bernouli equation.…”
Section: Introductionmentioning
confidence: 99%
“…To solve the equilibrium problem in the two elliptic regions, several computer codes have been developed (Semenzato et al 1984;Kerner and Tokuda 1987;Żelazny et al 1993). There is experimental evidence, however, that either the flow is purely toroidal (Suckewer et al 1979;Core et al 1987;Scott et al 1989;Tammen et al 1994) or its poloidal component is one order of magnitude lower than the toroidal one (Brau et al 1983). It was also found that the poloidal flow is efficiently damped by magnetic pumping (Hassam and Kulsrud 1978).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation